SAFETY PROBLEMS IN MARITIME TRANSPORT FROM THE POINT OF VIEW OF INFORMATION TECHNOLOGIES - Коновалов, Сергій (SWorldJournal, 2022)
Most of the international transport today is sea transport. In today's world, maritime transport plays a very important role. Any hazard capable of causing harm to the ship, goods or crew could be fatal. Modern ships use a lot of modern high-precision equ